1992
DOI: 10.1001/archderm.1992.01680120112014
|View full text |Cite
|
Sign up to set email alerts
|

Perianal Pseudoverrucous Papules and Nodules in Children

Abstract: Recognition of this entity is important because pseudoverrucous papules and nodules may mimic more serious dermatoses and unnecessary workup may be initiated. Although this reaction involving perianal skin has not been reported previously, we believe it is not uncommon.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(30 citation statements)
references
References 3 publications
1
29
0
Order By: Relevance
“…3,4,6 First described in association with irritation from urostomies 5,6 as wart-like papules or small, gray or brown, erosive papules, these lesions have subsequently been observed in the perianal, genital, suprapubic, and peristomal (urostomies and colostomies) areas and on the buttocks of infants and adults. 3,4,6 First described in association with irritation from urostomies 5,6 as wart-like papules or small, gray or brown, erosive papules, these lesions have subsequently been observed in the perianal, genital, suprapubic, and peristomal (urostomies and colostomies) areas and on the buttocks of infants and adults.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…3,4,6 First described in association with irritation from urostomies 5,6 as wart-like papules or small, gray or brown, erosive papules, these lesions have subsequently been observed in the perianal, genital, suprapubic, and peristomal (urostomies and colostomies) areas and on the buttocks of infants and adults. 3,4,6 First described in association with irritation from urostomies 5,6 as wart-like papules or small, gray or brown, erosive papules, these lesions have subsequently been observed in the perianal, genital, suprapubic, and peristomal (urostomies and colostomies) areas and on the buttocks of infants and adults.…”
Section: Discussionmentioning
confidence: 99%
“…Several pathogenic mechanisms seem to be involved. [3][4][5][6]11 The clinical differential diagnosis includes bacterial infections, viral warts, syphilitic condylomas, cutaneous Crohn disease, halogenodermas, necrolytic migratory erythema, and deficiency disorder (pellagra). 3,9 The process is favored in some cases by diaper coverings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Granuloma gluteale infantum is a rare dermatosis thought secondary to irritant dermatitis, candidiasis, occlusion, and prolonged use of benzocaine or fluorinated steroids [53]. Mainstays of treatment include controlling irritation, especially diarrhea, and good skin care of the diaper area similar to treatment of ICCD [54]. Biopsy to differentiate among condyloma, herpes simplex, molluscum contagiosum, granuloma gluteale infantum, and Langerhan's cell histiocytosis may be necessary [21].…”
Section: Complicationsmentioning
confidence: 99%
“…While it is well known that urea, pH, and maceration play a role in diaper dermatitis (2,3), the intermittent nature of most exposures and the fact that exposure is limited to young children protects the average patient from the development of Jacquet diaper dermatitis. Goldberg et al (4) reported on five patients, ages 15 months to 15 years, all with incontinence, who presented with pseudoverrucous nodules mimicking condyloma acuminatum. Other reports have linked incontinence to this entity, often a mimic of condyloma (5,6).…”
Section: To the Editorsmentioning
confidence: 99%